1990
DOI: 10.1063/1.104159
|View full text |Cite
|
Sign up to set email alerts
|

Observation of proposed flux pinning sites in neutron-irradiated YBa2Cu3O7−x

Abstract: Microstructure and magnetic hysteresis have been compared for two samples of the YBa2Cu3O7−δ (δ∼0) high-temperature superconductor, one unirradiated, and one irradiated with fast neutrons (E≳0.1 MeV) to a fluence of 3×1018 n/cm2. Notable changes in the microstructure include strain-induced contrast from regions 2–7 nm in size. An intrinsic critical current density (Jc) of 4.6×106 A/cm2 in zero field at 4 K has been determined from magnetic hysteresis measurements for the irradiated sample while 1.2×106 A/cm2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that fine-scale defects of a few nanometres can be artificially introduced into the HTS through neutron [68,69], proton [70], and heavy-ion 1711 irradiation. The J, of irradiated 123 single crystals has been shown to increase with irradiation fluence up to a certain maximum value before it decreases with further increase in fluence.…”
Section: Irradiation Damagementioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that fine-scale defects of a few nanometres can be artificially introduced into the HTS through neutron [68,69], proton [70], and heavy-ion 1711 irradiation. The J, of irradiated 123 single crystals has been shown to increase with irradiation fluence up to a certain maximum value before it decreases with further increase in fluence.…”
Section: Irradiation Damagementioning
confidence: 99%
“…The J, of irradiated 123 single crystals has been shown to increase with irradiation fluence up to a certain maximum value before it decreases with further increase in fluence. The defect structure is found to be small regions of vacancies created during irradiation, which may subsequently coalesce into defect clusters [69]. These regions are believed to possess a depressed superconducting order parameter with a characteristic spatial extent [70], and operate as effective flux-pinning centres due to their small dimensions.…”
Section: Irradiation Damagementioning
confidence: 99%